2022
DOI: 10.3390/fire5050149
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations on the Influencing Factors of Rapid Fire Spread of Flammable Cladding in a High-Rise Building

Abstract: This paper investigates aluminium composite panels (ACPs) to understand the fire behaviour of combustible cladding systems under different fire scenarios. A fire dynamics simulator (FDS) is used to develop the numerical model of full-scale fire tests of combustible cladding systems using the procedures of the British BS 8414.1 standards. The results obtained from the FDS models are verified with test data. Seven test scenarios are investigated with four distinct parameters, i.e., cavity barrier, air-cavity gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, Taylor's study [37], which includes fire spread through closed combustible cavities, indicated a reduction in vertical fire spread by reducing the cavity width. In the validated numerical study by Hassan et al [38], which simulated the BS 8414.1 façade fire test, using 50 mm and 100 mm cavity widths resulted in earlier failure times than the 25 mm cavity width due to the lack of oxygen in the 25 mm cavity. They believed that having a wide cavity produces less pressure for the fire plume to stretch up, thus resulting in increased fire spread.…”
Section: Fire Spread/combustionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Taylor's study [37], which includes fire spread through closed combustible cavities, indicated a reduction in vertical fire spread by reducing the cavity width. In the validated numerical study by Hassan et al [38], which simulated the BS 8414.1 façade fire test, using 50 mm and 100 mm cavity widths resulted in earlier failure times than the 25 mm cavity width due to the lack of oxygen in the 25 mm cavity. They believed that having a wide cavity produces less pressure for the fire plume to stretch up, thus resulting in increased fire spread.…”
Section: Fire Spread/combustionmentioning
confidence: 99%
“…Fire within the building [3,[6][7][8]11,14,15,17,19,25,33,35,[39][40][41]46,48,51,56,60,62,67,70] Fire initiated within the cavity [1,2,4,5,9,10,12,13,16,18,[28][29][30][31][32]36,37,57,71] External fire spread/events [16,28,37,38,41,43,47,59,62] Fire 2024, 7, 12…”
Section: Fire Scenariomentioning
confidence: 99%
“…Building fire disaster management systems in smart cities have become required due to the worldwide phenomenon of fire [14] and the increasing significance of fire accidents in structures [15]. So, this paper introduces a new energy-aware method to solve the problem of intelligent fire evacuation systems based on the IoT in smart buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional fire protection systems have many limitations [6,7]. Most high-rise building fires start as small local fires, gradually spreading to other locations and developing into large fires [8,9]. Thus, high-rise building fire protection systems need to detect and extinguish fires promptly, preventing small fires from escalating into large ones.…”
Section: Introductionmentioning
confidence: 99%